Rewrite as an expression that doesn't contain a fraction: (3tanX)/(1-cosX)

1 Answer | Add Yours

beckden's profile pic

beckden | High School Teacher | (Level 1) Educator

Posted on

 

`(3tanx)/(1-cosx)*(1+cosx)/(1+cosx)=(3tanx(1+cosx))/(1-cos^2x)=(3tanx+3tanxcosx)/(sin^2x) `

`tanx = sinx/cosx`

So

`(3tanx)/(1-cosx) = 3(sinx/cosx+sinx/cosx*cosx)/sin^2x=3(1/sinx1/cosx+1/sinx)`

`cscx=1/sinx` and `secx=1/cosx`   so

`(3tanx)/(1-cosx)=3cscx(secx+1)`

We’ve answered 315,786 questions. We can answer yours, too.

Ask a question